P08.08 Immunomodulation by Lactate dehydrogenase C indicates a potential new opportunity for combination therapy. (21st September 2022) - Naik, A; Thomas, R; Decock, J
Abstract : Background: Despite the success ofcancer immunotherapy in the treatment of advanced cancer, the clinical benefit is limited to a subgroup of patients. One of the major challenges remains the lack of a durable anti-tumor immune response within an immunosuppressive tumor microenvironment. Cancer testis antigens (CTAs) are lucrative anti-cancer targets with restricted expression patterns and defined roles in multiple cancer hallmarks. Lactate dehydrogenase C (LDHC) is a promising target with a highly tumor-specific expression that correlates with poor prognosis in breast cancer. We previously reported that silencing LDHC improves treatment response to DNA damage response drugs through dysregulation of the DNA damage response pathway. Here, we investigated the effect of LDHC silencing on the immune response to gain insight into the potential benefit of combining LDHC targeting with immunotherapy. Materials and Methods: Breast cancer transcriptomic data from TCGA and METABRIC were used to assess LDHC expression and association with cytotoxic T lymphocyte (CTL) infiltration. LDHC silencing of breast cancer cell lines was followed by analysis of immune-related gene expression (RT2 Profiler Cancer Inflammation & Immunity Crosstalk array), cytokine protein secretion (ProteomeProfiler cytokine antibody array) and immune checkpoint expression (flow cytometry). Finally, T cell activation within a co-culture model with LDHC-silenced cells was determined by IFN-γ ELISpot. Results: Transcriptomic analysis demonstrated a higher LDHC expression in basal-like and HER2-enriched breast tumors than in luminal tumors, and a significantly poorer overall and disease-specific survival for LDHC expressing tumors. Tumor Immune Dysfunction and Exclusion (TIDE) analysis showed that high LDHC expression in Her2 (TIDE score=1.97, p=0.049) and triple negative breast tumors (TIDE score=0.466, p=0.642) dampens the beneficial effect of CTLs on overall survival. Concurrently, LDHC silencing of breast cancer cells induced substantial dysregulation of immunosuppressive cytokines. Furthermore, gene ontology analysis of differentially expressed immune-related genes and secreted cytokines predicted that LDHC silencing upregulates the granzyme-mediated cell death pathway; T cell proliferation, activation and differentiation; cytolysis and interferon gamma production while downregulating TLR signaling pathway, macrophage activation, natural killer cell activation, and monocyte and lymphocyte chemotaxis. In addition, LDHC silencing reduced the expression of the PD-L1 and Gal-9 immune checkpoint ligands, suggesting additional levels of immunomodulation. In line with these observations, functional analysis confirmed that LDHC silencing affects T cell activation in a co-culture setting. Conclusions: Our current findings suggest that targeting LDHC may have a dual anti-cancer benefit, impairing tumor cell survival while supporting a favorable tumor immune microenvironment. As such, LDHC-based therapy could potentially improve clinical outcome when used in combination with DNA damage response drugs or immunotherapy. Disclosure Information: A. Naik: None. R. Thomas: None. J. Decock: None.